Is there a safe time to stop clopidogrel in patients on dual antiplatelet therapy after a percutaneous coronary intervention and placement of drug-eluting stents? - Almaddah, Nureddin; Khouzam, Rami N. (Journal of Thoracic Disease, 2017)
No clear evidence determines the most effective duration for dual antiplatelet therapy (DAPT) after drug-eluting stents (DES). Although DES reduces the rate of restenosis compared with bare-metal stents (BMS), it is of concern that they may be associated with a risk of stent thrombosis beyond 1 year post treatment. Many randomized clinical trials demonstrated the effectiveness of DAPT in preventing stent thrombosis; a serious complication of PCI. Additionally, it is believed that DAPT prevents adverse occurrences consequent to plaque rupture at a location other than the stented one. Such are the results of a study that compared medical treatment of acute coronary syndrome with Aspirin versus DAPT with clear reduction in the rate of myocardial infarction (MI) in patients who received DAPT (1).